Epilepsy and Autism Spectrum Disorder (ASD): The Underlying Mechanisms and Therapy Targets Related to Adenosine - Guo, Mengyi; Xie, Pandeng; Liu, Siqi; Luan, Guoming; Li, Tianfu (Current Neuropharmacology, 2023)
Epilepsy and autism spectrum disorder (ASD) are highly mutually comorbid, suggesting potential overlaps in genetic etiology, pathophysiology, and neurodevelopmental abnormalities. Adenosine, an endogenous anticonvulsant and neuroprotective neuromodulator of the brain, has been proved to affect the process of epilepsy and ASD. On the one hand, adenosine plays a crucial role in preventing the progression and development of epilepsy through adenosine receptordependent and -independent ways. On the other hand, adenosine signaling can not only regulate core symptoms but also improve comorbid disorders in ASD. Given the important role of adenosine in epilepsy and ASD, therapeutic strategies related to adenosine, including the ketogenic diet, neuromodulation therapy, and adenosine augmentation therapy, have been suggested for the arrangement of epilepsy and ASD. There are several proposals in this review. Firstly, it is necessary to further discuss the relationship between both diseases based on the comorbid symptoms and mechanisms of epilepsy and ASD. Secondly, it is important to explore the role of adenosine involved in epilepsy and ASD. Lastly, potential therapeutic value and clinical approaches of adenosine-related therapies in treating epilepsy and ASD need to be emphasized.
Keywords: ketogenic diet